Product-Service Systems across Industry Sectors: Future Research Needs and Challenges - Durugbo, Christopher; Bankole, O. O.; Erkoyuncu, John Ahmet; Tiwari, Ashutosh; Alcock, Jeffrey R.; Roy, Rajkumar; Shehab, Essam (Cranfield University, 2010)
This paper explores the current research in Product-Service Systems (PSS) across various industries suchas industrials, basic materials, utilities, and financials, based on the Industry Classification Benchmark (ICB).PSS elements are identified within each industry in terms of tangible and intangible elements of productsand services. Based on this identification, the differences in PSS delivery across industry sectors aredefined based on two sources namely (i) actors, relationships, and networks, and (ii) delivery packages.Founded on the differences identified, the paper explains future research needs and challenges with focuson the scope of PSS, intra- and inter- sector flows and interactions between actors involved in PSS deliveryand PSS design.